VAMDC as a Resource for Atomic and Molecular Data and the New Release of VALD - Kupka F. (Open Astronomy, 2011)
The Virtual Atomic and Molecular Data Centre (VAMDC) is an EU-FP7 project devoted to build a common electronic infrastructure for the exchange and distribution of atomic and molecular data. Within VAMDC scientists from many different disciplines in atomic and molecular physics collaborate with users of their data and also with scientists and engineers from the information and communication technology community. In this presentation, an overview of the current status of VAMDC and its capabilities is provided. In the second part of the presentation I will focus on one of the databases which have become a part of the VAMDC platform, the Vienna Atomic Line Data Base (VALD). VALD has developed into a well-known resource of atomic data for spectroscopy, particularly in astrophysics. A new release, VALD-3, will provide numerous improvements over its predecessor. This particularly relates to the data contents where new sets of atomic data for both precision spectroscopy (i.e., with data for observed energy levels) as well as opacity calculations (i.e., with data involving predicted energy levels) have been included. Data for selected diatomic molecules have been added, and the new system for data distribution and data referencing provides more convenience in using the third release of VALD.